Stereotypes and Bias at the Psychiatric Bedside - Cultural Competence in the Third-Year Required Clerkships - Donna Elliott; Cheryl St. George; Darin Signorelli; Janet Trial (Association of American Medical Colleges, 2010)
Abstract Building on a foundation of cultural awareness, knowledge, and skills that medical students have acquired during their first and second years, this clinical curriculum provides an opportunity for students to continue to refine their cultural competency clinical skills as they practice their medical interpretation skills at the bedside. This resource includes a didactic presentation, a clinical reflection experience, and a small-group discussion. Cultural competence education begins with a focus on building cultural self-awareness and acquiring cultural knowledge as the first stages in a developmental process that leads to cultural competence. The explanatory model of illness and the philosophy of patient-centered care should guide this progression. Cultivating effective cross-cultural communication skills requires an understanding of culture that includes both the physician's and the patient's perspectives. Integrating cultural competence into the clinical clerkship allows students to apply cultural competence knowledge gained in the first 2 years of medical education, as well as to develop clinical skills in caring for patients with a variety of cultural backgrounds. Feedback on student essays creates a dialogue between faculty and students that augments this learning experience.